Comparative analysis of users' awareness and attitudes towards the reference services in academic libraries - Dalina, Daisy S.; Ramos, Marian S. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study was conducted to find out the user's awareness and attitudes towards the reference services of Baliuag University Library and University of Santo Tomas Central Library. This study searched answers to the following questions: (1) Who are the frequent users of the reference section of the library? (1) What are the users' levels of awareness of the reference services? (3) What are the attitudes of the users toward the reference services? (4) What are factors influencing the awareness and attitude of the users toward the reference services offered by the Baliuag University Library and University of the Santo Tomas Central Library? (5) What is the relationship between the age, sex, use of reference section and frequency of use of reference services of the respondents' attitude level? (7) What are the comments/suggestions of the users towards the improvement of the existing reference services in the library?
The population of the study includes two hundred and forty nine (249) library users who used the reference services of the two academic libraries within four consecutive days in April 2005 when the survey was made. The descriptive survey method was used having the survey questionnaire as the research instrument. In the analysis of data, the weighted mean and frequency distribution were used with the help of SPSS version 12. To test the hypotheses, the T-test and ANOVA was employed.
According to the findings of the study, both the academic libraries perform various reference services and these affect the user's attitudes and awareness towards these services. Factors such as age, sex, use and frequency of use of the reference section and its services have relationship with the respondents' level of awareness and attitudes towards the reference services.
As indicated by the responses and statistical measures, whatever the factors affecting their use, attitude and awareness of the reference services, the users are aware and have positive attitude towards the reference services of their respective libraries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Bulacan (Baliuag).; Academic libraries -- Philippines -- Manila; Reference services (libraries) -- Philippines -- Manila; Reference services (Libraries) -- Philippines -- Bulacan (Baliuag).